2016
DOI: 10.4103/0971-6203.177287
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computed tomography dose index in polymethyl methacrylate and nylon dosimetry phantoms

Abstract: The use of computed tomography (CT) scanning has been growing steadily. Therefore, CT dose measurement is becoming increasingly important for patient protection and optimization. A phantom is an important tool for dose measurement. This paper focuses on the evaluation of a CT dosimetry phantom made from nylon, instead of the standard polymethyl methacrylate (PMMA), which is not readily available or is too expensive in some countries. Comparison between phantoms made from the two materials is made in terms of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…This material reduced the production cost to about one-fifth of that of the standard PMMA phantom. The results demonstrated that the CT number of the nylon phantom was 20 HU lower than that of the standard PMMA phantom [20], yet the findings of this study have provided convincing results.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…This material reduced the production cost to about one-fifth of that of the standard PMMA phantom. The results demonstrated that the CT number of the nylon phantom was 20 HU lower than that of the standard PMMA phantom [20], yet the findings of this study have provided convincing results.…”
Section: Discussionmentioning
confidence: 63%
“…Hence, the differences in CT number measured between the polyester resin and the standard PMMA phantom were less than 10 HU. This indicated that the polyester resin is more suitable than nylon as an alternative phantom [20].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The HUs were obtained for both 80 and 140 kV spectra, and for the number of histories of 10 9 and 10 10 . Sookpeng et al (Sookpeng et al, 2016). In this case, the authors found CT numbers for nylon from 60 HU to 117 HU for different phantom sizes and energies.…”
Section: Contrast To Noise Ratio Cnr and Signal To Noise Ratio Snrmentioning
confidence: 75%